Penerapan Hukum Islam dalam Konteks Indonesia: Interaksi dengan Sistem Hukum Nasional dan Tantangan Pengembangannya - Br Saragih, Nadia; Al Syahra, Tania; Syukri Azhari, Devi (UNIVERSITAS SERAMBI MEKKAH, 2025)
system and its role in the social and cultural life of the community. Indonesia, with the largest Muslim population in the world, presents a unique context where Islamic law is integrated into the national legal framework. The study aims to provide a deeper understanding of the position of Islamic law in Indonesia, highlighting the areas where it is implemented, such as marriage, inheritance, and Islamic economics. The article also explores the challenges and opportunities in harmonizing Islamic law with national law, particularly in the context of pluralism and religious diversity. Through document analysis, interviews with legal experts, and case studies from various regions, this research identifies the ongoing debates surrounding the application of Islamic law and its potential for development in the future. The findings suggest that while Islamic law plays a significant role in the lives of Indonesian Muslims, a constructive dialogue is necessary to ensure its balanced implementation within the framework of national law.